Some elliptic equations with W01, 1 solutions. (April 2017) - Boccardo, Lucio; Cirmi, G. Rita
Abstract: We consider some nonlinear Dirichlet problems and we study how lower order terms can give a regularizing effect on the solutions: the existence of distributional solutions with minimal properties (solutions in W 0 1, 1, functional space not so usual for finding solutions of elliptic problems) or finite energy solutions, even with nonregular data.